Sustainability Assurance, Carbon Emissions Performance and Reporting Quality of Carbon Intensive Industry in Sub-Saharan Africa - Jabar, Adebola Abass; Adeosun, Oluwaseun T. (Journal of Sustainable Development Law and Policy, 2024)
The quality of the sustainability report published across organisations has consistently been questioned over the years. In response, organisations have been increasing the credibility of their sustainability report through external assurance. This study examines the association between Sustainability Assurance (SA); big-4 and Sustainability Reporting Quality (SRQ) as well as examines the moderating effect of Carbon Emission Performance (CEP) between sustainability assurance and reporting quality of carbon intensive industry in sub-Saharan Africa. Ex-post facto research design was used. The population is 332 listed organisations. The population represents the sample size with the use of census sampling technique. The findings reveal that SA and the use of big-4 both improve SRQ. On the other hand, CEP does not moderate the association between SA and SRQ as CEP and SA both individually improve SRQ. The study offers a practical implication on the importance of SA in improving reporting quality in sub-Saharan Africa given the peculiarity of the region; it educates organisations in the region on the advantage they stand to benefit in publishing quality sustainability reports. It is also expected to improve the orientation of organisations and internal stakeholders towards SRQ as the adoption of SA benefits the stakeholders more through attraction of more investment. The findings also suggest to the government how the existence of a standard institutional framework will be helpful to organisations.